Longitudinal association between poor parental supervision and risk‐taking behavior: The role of self‐control and school climate - Dou, Kai; Wang, Lin‐Xin; Cheng, Dan‐Li; Li, Yan‐Yu; Zhang, Ming‐Chen (Journal of adolescence (London, England.), 2022)
Introduction Although poor parental supervision has been associated with an increased adolescents' propensity for risk‐taking behavior, few researchers have investigated nuanced mechanisms of how and for whom from the perspective of “family × school.” Inspired by ecological system theory and self‐control theory, this study aimed to investigate the mediating role of self‐control and the moderating role of school climate between the link between poor parental supervision and risk‐taking behavior. Methods Four hundred and ninety‐one Chinese adolescents (231 females, Mage = 15.39 ± 1.36) were recruited to participate in a three‐wave longitudinal study (3 months apart) and complete questionnaires regarding poor parental supervision (W1), school climate (W1), self‐control (W2), and risk‐taking behavior (W1/W3). Results After controlling for W1 risk‐taking behavior, our moderated mediation model indicated that W1 poor parental supervision was positively related to W3 risk‐taking behavior by restraining the development of W2 self‐control. Additionally, a high level of school climate as a protective factor buffered the negative impact of poor parental supervision on adolescents' self‐control, further reducing risk‐taking behavior. Conclusion Our findings shed light on the processing mechanisms between poor parental supervision and risk‐taking behavior among Chinese adolescents and underscore the importance of effective preventions and interventions to facilitate adolescents' healthy development.